Predicting the Intention to Pursue Certified Professional Accountancy Qualification Among the Accounting Students - Chi, Tiw Kai; Sin Yi, Thai; Al Mamun, Abdullah; Hayat, Naeem; Salamah, Anas A.; Yang, Qing (Frontiers in Psychology, 2022)
The global progress empowers the development of new business and expansion of existing business. The availability of sufficient accounting professional are necessary to manage and document the business activities. However, youth are less inclined to purse accounting as profession to keep the progress of global and local economic development. The current study aimed to explore the formation of the intention to pursue Certified Professional Accountancy Qualification (CPAQ) with factor of capabilities, career opportunities, job security with respect to the extended theory of planned behavior (TPB), i.e., attitude, subjective norms and perceived behavioral control. The study adopted a cross-sectional design and collected quantitative data from a total of 339 accounting students from Malaysia using an online survey. The finding revealed that capabilities and career opportunities influenced the students’ intention to pursue CPAQ. Meanwhile, perceived behavioral control had significantly affect the students’ decision to pursue CPAQ, which is in line with the TPB. The study concentrated on the importance of these factors in influencing the students’ intention and decision to pursue CPAQ. The study offered vital implications for accounting educators and educational institutions to promote the accounting profession as choice and students engage in pursuing CPAQ. The Malaysian government should encourage and support accounting students financially for pursuing CPAQ by providing job security and enhancing subjective norms that may enable these students to complete the required professional qualifications. The study’s limitations and future research opportunities are documented at the end of this article.